2014
DOI: 10.1177/2150135114549748
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Preoperative Angiotensin-Converting Enzyme Inhibitor and Angiotensin II Receptor Blocker Use on Hemodynamic Variables in Pediatric Patients Undergoing Cardiopulmonary Bypass

Abstract: The use of preoperative ACE inhibitors and ARBs in pediatric patients undergoing cardiac surgery did not significantly increase the incidence of hypotension after induction of anesthesia and did not increase significantly the vasoconstrictor requirements upon weaning from cardiopulmonary bypass; however, additional prospective studies are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…38 The presurgical management of these drugs in children is not well characterized, with most centers advising discontinuation the day before surgery if possible. 39 Low-dose aspirin is often well tolerated during superficial surgical procedures but is held ≥5 days before major surgical procedures because of the potential for bleeding. 40 In contrast, patients on warfarin may need to be either transitioned to subcutaneous therapy in the outpatient setting or admitted for conversion to intravenous heparin.…”
Section: Preoperative Evaluation Before Noncardiac Surgerymentioning
confidence: 99%
“…38 The presurgical management of these drugs in children is not well characterized, with most centers advising discontinuation the day before surgery if possible. 39 Low-dose aspirin is often well tolerated during superficial surgical procedures but is held ≥5 days before major surgical procedures because of the potential for bleeding. 40 In contrast, patients on warfarin may need to be either transitioned to subcutaneous therapy in the outpatient setting or admitted for conversion to intravenous heparin.…”
Section: Preoperative Evaluation Before Noncardiac Surgerymentioning
confidence: 99%
“…The association between angiotensin converting enzyme inhibitors (ACEI) and post-operative hypotension was first recognized more than two decades ago in adults ( 6 , 7 ). In a previous study Ajuba-Iwuji et al reported that preoperative ACE inhibitor and ARB use in pediatric patients undergoing cardiac surgery did not significantly increase the incidence of hypotension after induction of anesthesia and did not significantly increase vasoconstrictor requirements upon weaning from CPB; however, patients on ACE inhibitor/ARB therapy tended to have a higher VIS than patients in the control group ( 8 ). This study has important limitations acknowledged by the authors including small and discrepant sample size (18 vs. 132), unmatched groups of patients, different mean age (6.4 ± 6.1 years vs. 4.3 ± 5.5 years), unmatched diagnosis, potential of under reporting and recording bias and combining patients taking ACEI and ARB into one group (both these drugs act at different levels).…”
Section: Discussionmentioning
confidence: 98%